Effect of breed, sex, and age on the body and internal organ weight of chickens for food security in resource-poor communities of KwaZulu-Natal, South Africa - Tenza, Thando; Mhlongo, Lindokuhle Christopher; Ncobela, Cyprial Ndumiso; Rani, Zikhona (Frontiers in Animal Science, 2025)
IntroductionThis study aimed to compare the effects of sex, breed, and age on the body weight and internal organ weight of chickens reared in resource-poor communities. Understanding these factors is important for optimizing poultry production and enhancing food security in such environments.MethodsA total of 120 chickens were used, comprising three breeds: broilers (n=40), Potchefstroom Koekoek (n=40), and a non-descriptive breed (n=40). Each breed group consisted of 20 males and 20 females, which were further categorized by age into 10 growers and 10 mature chickens per breed. Body weight and internal organ weights (liver, gizzard, heart, intestinal weight, and length) were measured and analyzed to assess the influence of breed, sex, and age.ResultsThe results indicated that both grower and mature broilers had the highest body weights compared to Potchefstroom Koekoek and the non-descriptive breed. Breed significantly influenced body weight (p<0.001), and males were generally heavier than females, although this difference was not statistically significant (p>0.05). Liver weight was higher in females, but sex did not significantly affect liver weight. A linear relationship (p<0.05) was observed between body weight and the variables breed, sex, and age. Breed had a negative coefficient with body weight, while sex and age had positive coefficients. Age demonstrated the strongest relationship with both body weight and liver weight. The independent variables (breed, sex, and age) accounted for 64% of the variance in body weight.DiscussionThe findings demonstrate that breed and age are significant determinants of body weight and internal organ weight in chickens reared under resource-poor conditions, whereas sex has a lesser effect. These results highlight the importance of considering breed and age in poultry management strategies to maximize meat and organ yield, thereby contributing to food security. Further research is recommended to explore these relationships in greater depth, with a focus on the potential of chickens in resource-poor communities, regardless of breed, sex, or age.